THE INFLUENCE OF CELEBRITY ENDORSEMENT ON PURCHASE INTENTION K-MEALS MCDONALD'S: THE ROLE OF BRAND CREDIBILITY - Ezra, Anggriana; Firdausy, Carunia Mulya (Graduate Program of Universitas Tarumanagara, 2024)
This research aims to analyze the influence of celebrity endorsement, brand credibility, and purchase intention on consumers of McDonald's K-Meals products. The study's population consists of consumers of K-Meals McDonald’s products in the Jakarta, Depok, Tangerang, and Bekasi area. The sampling method used was non-probability sampling with a purposive sampling technique for 120 respondents and the data was analyzed using descriptive analysis methods. The research instrument testing includes outer model testing, inner model testing, and hypothesis testing using smartPLS-SEM 4.0. The results of this study indicate that celebrity endorsements directly influence the purchase intention of K-Meals McDonald’s products. Brand credibility positively mediates the relationship between celebrity endorsement and purchase intention for McDonald's K-Meals products. McDonald's is expected to be able to optimize promotional strategies by using celebrity endorsements which can strengthen McDonald's brand credibility to meet market preferences and needs in Indonesia.